Design of Car Battery Protection Device Based on Torsion Spring - 张东明 张晓云 杨智淳 俞骏威 (Shanghai jiao tong da xue xue bao, 2017)
In recent years, electric vehicles are developing rapidly in automotive industry. When involved in accidents, if the batteries of electric cars break, it is likely to cause a short circuit and start a fire. Aimed at this issue, a car battery protection device based on torsion spring has been designed. The car battery protection device can deform in a particular pattern in a collision accident. Impact energy of the accident is absorbed by the deformation, which can significantly reduce impact force on the batteries. Meanwhile, based on the principle of maximum energy absorption, some crucial parameters of the device can be determined. Furthermore, an impact simulation conducted on ANSYS software shows that maximum safety factors can be obtained when the material of car battery protection device is carbon steel. The analysis of “safe space” in the car battery protection device shows that the device can prevent battery damage effectively in general circumstances, which means the reliability of the device has been verified. Therefore, when applied to electric vehicles, the car battery protection device,which can prevent secondary accidents, significantly improves the vehicle security in accidents.